1969
DOI: 10.1139/z69-210
|View full text |Cite
|
Sign up to set email alerts
|

Numbers of granulocytes in thymic imprints of rabbits of different ages and degrees of coccidial parasitism

Abstract: Counts of granulocytes were performed on thymic imprints from normal rabbits 3 days old, 2–3 weeks old, and young adults, and from young adult rabbits mildly and severely parasitized with coccidiosis. Analyses of percentages of eosinophils, heterophils, and basophils indicated no sex differences. Comparisons of relative numbers of granulocytes in normal rabbits showed that young adult rabbits possessed more eosinophils and fewer basophils than the younger groups (no differences in heterophils); 3-day-old rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Granulopoiesis is the thymus has been extensively documented since the late 1800s (see Bhatal and Campbell, 1965). More recently, granulocyte development has been shown in rodents (Sin and Sainte-Marie 1965;von Haelst, 1967;Kendall and Blackett, 1983;Kendall et al, 1985;Boshnakova, 1990) humans (Downey, 1948;Bhatal and Campbell, 1965), cats (Pack and Chapman, 1980), and rabbits (Downey, 1948;Westermann and Engelbert, 1969a, 1969b, 1969c. The embryonic and fetal stages of many animals show development of granulocytes within the thymus, and this activity may continue into adult life.…”
Section: Other Granulocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulopoiesis is the thymus has been extensively documented since the late 1800s (see Bhatal and Campbell, 1965). More recently, granulocyte development has been shown in rodents (Sin and Sainte-Marie 1965;von Haelst, 1967;Kendall and Blackett, 1983;Kendall et al, 1985;Boshnakova, 1990) humans (Downey, 1948;Bhatal and Campbell, 1965), cats (Pack and Chapman, 1980), and rabbits (Downey, 1948;Westermann and Engelbert, 1969a, 1969b, 1969c. The embryonic and fetal stages of many animals show development of granulocytes within the thymus, and this activity may continue into adult life.…”
Section: Other Granulocytesmentioning
confidence: 99%
“…In many avian thymuses, mature eosinophils were found within vacuoles in or close to the necrotic center of Hassall's corpuscles (Kendall and Frazier, 1979). Associations of this nature were also observed in children (Bhatal and Campbell, 1965;Muller, 1977) and in rabbits (Westermann and Engelbert, 1969b). It has been suggested that they may be phagocytosing antigen-antibody complexes at this site because both antigen (Marshall and White, 1961) and immunoglobulins (Henry and Anderson, 1990) Several important questions arise from this activity.…”
Section: Other Granulocytesmentioning
confidence: 99%